FAKTOR-FAKTOR YANG MEMENGARUHI STRES KERJA PADA PERAWAT DI RUANG RAWAT INAP - Hartati Zuraidah Rangkuti; Juliandi Harahap; Asyiah Simajorang (Jurnal Keperawatan Priority, 2022)
The stress nurses face in hospitals at work will greatly affect the quality of nursing services provided to patients. This study aims to analyze what factors affect the work stress on nurses. This research is a quantitative study with a research design using the analytical survey method with a Cross Sectional approach. The research was conducted at Rantauprapat Hospital, Labuhanbatu Regency. The sample was 82 nurses obtained by purposive sampling. Data analysis was performed using a univariate analysis test, Bivariate using a chi-square test, and Multivariate using multiple Logistic regression. The results showed that in the univariate analysis of 82 respondents, most of the respondents were 36-45 years old, namely 36 (43.9%), and had a D3 Nursing education level, namely 45 (54.9%). In the Bivariate analysis, it was found that there was the effect of workload on nurses' work stress (p= 0.000), there was an effect of the work environment on nurses' work stress (p= 0.000), there an effect of career development on nurse stress (p= 0.000), there was the effect of role conflict double the work stress of nurses (p= 0,000). In the multivariate analysis, the most dominant variable affecting the work stress of nurses was career development with a p value of 0.007, t count = 2.273 (r table = 0.2146). Based on the results of this study, it is recommended that the hospital provide the duties and responsibilities given should not be less or excessive so that work stress on nurses.